-0.6y+1.3=4.5-0.2y

Simple and best practice solution for -0.6y+1.3=4.5-0.2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.6y+1.3=4.5-0.2y equation:


Simplifying
-0.6y + 1.3 = 4.5 + -0.2y

Reorder the terms:
1.3 + -0.6y = 4.5 + -0.2y

Solving
1.3 + -0.6y = 4.5 + -0.2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '0.2y' to each side of the equation.
1.3 + -0.6y + 0.2y = 4.5 + -0.2y + 0.2y

Combine like terms: -0.6y + 0.2y = -0.4y
1.3 + -0.4y = 4.5 + -0.2y + 0.2y

Combine like terms: -0.2y + 0.2y = 0.0
1.3 + -0.4y = 4.5 + 0.0
1.3 + -0.4y = 4.5

Add '-1.3' to each side of the equation.
1.3 + -1.3 + -0.4y = 4.5 + -1.3

Combine like terms: 1.3 + -1.3 = 0.0
0.0 + -0.4y = 4.5 + -1.3
-0.4y = 4.5 + -1.3

Combine like terms: 4.5 + -1.3 = 3.2
-0.4y = 3.2

Divide each side by '-0.4'.
y = -8

Simplifying
y = -8

See similar equations:

| 9x+2=152 | | -3x+11=-2x+6 | | 38=y-39 | | -8=5+s | | 22x-43=14x-17 | | 6x^2+14x-4=0 | | y+42=100 | | 1.6=3y+14.5 | | -7x-3x+2=8-8x-8 | | 12+6w=0 | | 18x-120=10x-72 | | 9999999999999999999999999999999999999999999999999999+99999999999999999999999999999999999999999999999999= | | F(X)=(2x-1)(x+3)(x-2) | | p=50-8x+3x^2 | | 4=52/f | | 15=-7/8(45-X) | | 3z=1.3+2.9 | | f+27=42 | | 3d+5=5-10 | | 4=6+a | | -6n+21= | | r-25=49 | | 5y+12=42 | | 0.09xX=51.29 | | m-37=49 | | 44=h-33 | | 8/x=12/3 | | 8w-15w=35 | | 55=k-29 | | Y/3.5=10 | | 41=y+19 | | y-7=2.66(x-10) |

Equations solver categories